Pengaruh Electronic Word of Mouth Dan Customer Experience Terhadap Brand Trust UD. Mahameru Motor - Rafikhein Novia Ayuanti; Reyhan Alya Natalie (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to find out how electronic word of mouth, customer experience, and brand trust influence partially or simultaneously at UD. Mahameru Motor Kediri data used in research consists of several questionnaires, documentation, interviews, surveys, and several literature studies that are still related to research. Data analysis uses the SPSS program with analysis techniques of validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, coefficient of determination. From the research results, it is known that electronic word of mouth has an effect on brand trust with a sig t value of 0.021 < 0.05. Customer experience influences brand trust with a sig t value of 0.000 < 0.05. Electronic word of mouth and customer experience influence brand trust with a sig F value of 0.000 < 0.05.